2011
DOI: 10.1159/000331747
|View full text |Cite
|
Sign up to set email alerts
|

Chronic β-adrenoceptor Antagonists Upregulate the Rat Alveolar Macrophage Adrenergic System Through the β<sub>1</sub>-Subtype

Abstract: Background: Previous studies demonstrate that macrophages synthesis and release catecholamines, which regulate the immune responses in an autocrine manner. These responses are mediated in part by β-adrenoceptors expressed on macrophages. Some β-adrenoceptor antagonists are commonly used in clinical conditions. Here we investigated whether the chronic administration of β-adrenoceptor antagonists upregulate adrenergic system of alveolar macrophage and the potential mechanims. Methods: Propranolol (30 mg/kg·d) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These age-related decreases were prevented by atenolol in Old-AT mice. Atenolol increases various activities of immune cells in vitro (Guo et al ., 2011 ), but this had not been described previously in vivo .…”
Section: Discussionmentioning
confidence: 64%
“…These age-related decreases were prevented by atenolol in Old-AT mice. Atenolol increases various activities of immune cells in vitro (Guo et al ., 2011 ), but this had not been described previously in vivo .…”
Section: Discussionmentioning
confidence: 64%
“…Inhibition of the β-adrenergic receptor with the β-blocker propranolol, or depletion of adrenal catecholamines by adrenalectomy, led to increased LPS-induced tumor necrosis factor (TNF) α production in peritoneal macrophages [12]. Alveolar macrophages recovered from mice chronically treated with β-blockers produced more noradrenaline, interleukin (IL) 6 and TNFα following LPS treatment ex vivo [13]. Conversely, adrenaline, noradrenaline and dopamine treatment of RAW 264.7 macrophages inhibited LPS-induced production of nitric oxide [14].…”
Section: Catecholaminesmentioning
confidence: 99%
“…They proposed that b 1 -AA mediates catecholamine-like actions leading to the beating rate in spontaneously beating neonatal rat cardiomyocytes [Jane-wit et al, 2007]. It has been reported that catecholamines can either activate [Guo et al, 2011;Nguyen et al, 2011] or suppress [Hasko et al, 1998;Zinyama et al, 2001] macrophage functions, such as the secretion of cytokines. Furthermore, published papers demonstrated that b 1 -adrenergic receptor (b 1 -AR) is expressed on the surface of RAW264.7 cells [Sun et al, 2005].…”
mentioning
confidence: 99%